A novel in silico antimicrobial peptide DP7 combats MDR Pseudomonas aeruginosa and related biofilm infections. (31st July 2020) - Yin, Qi; Wu, Siwen; Wu, Lei; Wang, Zhenling; Mu, Yandong; Zhang, Rui; Dong, Chunyan; Zhou, Bailing; Zhao, Binyan; Zheng, Jiajun; Sun, Ying; Cheng, Xingjun; et al.
Abstract: Background: Antimicrobial peptides are promising alternative antimicrobial agents to combat MDR. DP7, an antimicrobial peptide designed in silico, possesses broad-spectrum antimicrobial activities and immunomodulatory effects. However, the effects of DP7 against Pseudomonas aeruginosa and biofilm infection remain largely unexplored. Objectives: To assess (i) the antimicrobial activity of DP7 against MDR P. aeruginosa ; and (ii) the antibiofilm activity against biofilm infection. Also, to preliminarily investigate the possible antimicrobial mode of action. Methods: The MICs of DP7 for 104 clinical P. aeruginosa strains (including 57 MDR strains) and the antibiofilm activity were determined. RNA-Seq, genome sequencing and cell morphology were conducted. Both acute and chronic biofilm infection mouse models were established. Two mutants, resulting from point mutations associated with LPS and biofilms, were constructed to investigate the potential mode of action. Results: DP7, at 8–32 mg/L, inhibited the growth of clinical P. aeruginosa strains and, at 64 mg/L, reduced biofilm formation by 43% to 68% in vitro . In acute lung infection, 0.5 mg/kg DP7 exhibited a 70% protection rate and reduced bacterial colonization by 50% in chronic infection. DP7 mainly suppressed gene expression involving LPS and outer membrane proteins and disrupted cell wall structure. Genome sequencing of the DP7-resistant strain DP7R revealed four SNPs controlling LPS and biofilm production. gshA44 and wbpJ139 mutants displayed LPS reduction and motility deficiency, conferring the reduction of LPS and biofilm biomass of strain DP7R and indicating that LPS was a potential target of DP7. Conclusions: These results demonstrate that DP7 may hold potential as an effective antimicrobial agent against MDR P. aeruginosa and related infections.